Simon Ernest Sobeloff papers - Sobeloff, Simon Ernest, 1894-1973.
Correspondence, appointment books, solicitor general files, case and office files of the U.S. Court of Appeals, speeches and writings, subject file, and miscellany relating to Sobeloff's involvement in Baltimore and Maryland law and politics, his duties as solicitor general (1954-1955), especially actions concerning school desegregation and the Subversive Activities Control Board, cases heard before the Fourth Circuit U.S. Court of Appeals (1956-1973), his associations with the American Bar Association, the National Council on Crime and Delinquency, the Baltimore Urban League, and various Jewish groups, including the American Jewish Congress. Includes three reels of microfilm reproducing 14 volumes of scrapbooks (1914-1972).
Correspondents include David L. Bazelon, Warren E. Burger, William O. Douglas, Dwight D. Eisenhower, Felix Frankfurter, Clement F. Haynsworth, J. Edgar Hoover, Jacob K. Javits, Robert F. Kennedy, Harold Leventhal, Theodore R. McKeldin, H. L. Mencken, John Johnston Parker, John Paul, Morris Ames Soper, R. Dorsey Watkins, and J. Skelly Wright.
Microfilm edition of scrapbooks available
Microfilm of scrapbooks produced from originals in private hands.
Private
Lawyer, U.S. solicitor general, and federal judge.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bazelon, David L. -- Correspondence; Burger, Warren E., -- 1907-1995 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Haynsworth, Clement F. -- 1912-1989 -- Correspondence; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Javits, Jacob K. -- 1904-1986 -- Correspondence; Kennedy, Robert F., -- 1925-1968 -- Correspondence; Leventhal, Harold, -- 1915-1979 -- Correspondence; McKeldin, Theodore R. -- 1900-1974 -- Correspondence; Mencken, H. L. -- 1880-1956 -- Correspondence; Parker, John Johnston, -- 1885-1958 -- Correspondence; Paul, John, -- 1883-1964 -- Correspondence; Soper, Morris Ames, -- 1873-1963 -- Correspondence; Watkins, R. Dorsey -- 1900-1986 -- Correspondence; Wright, J. Skelly -- Correspondence; United States. -- Court of Appeals (4th Circuit); United States. -- Solicitor General; United States. -- Subversive Activities Control Board; American Bar Association; American Jewish Congress; Baltimore Urban League (Md.); National Council on Crime and Delinquency; Courts -- United States; Jews -- Societies, etc; Law -- Maryland; Law -- Maryland -- Baltimore; Law -- United States -- Cases; Race relations; School integration; Segregation in education; Baltimore (Md.) -- Politics and government; Maryland -- Politics and government; Jurists; Lawyers; Public officials